Tuberculous Lymphadenitis coexists with Non-Hodgkin Lymphoma - Nenci Siagian; Bramantono Bramantono; Usman Hadi (Universitas Airlangga, 2020)
Tuberculous Lymphadenitis (TBLN) is most common extrapulmonary tuberculosis. The common symptom of TBLN is cervical lymphadenopathy which is known to mimic numerous pathological conditions like NHL. Coexistency TBLN and lymphoma is a rare. A woman, 56 years old, had chief complaint of cervical masses since 2 months ago. She had history of weight loss, fever and night sweats but no history of chronic cough. From physical examination and supporting examination, the patient was diagnosed with TBLN coexists with NHL. She got antituberculosis drug (ATD) for 2 weeks before chemotherapy. The patient died of septic shock 9 days later after chemotherapy. From HPE examination, TBLN and NHL may show simillar feature so Zhiel-Neelsen staining and Immunohistochemical are important to confirm each disease. ATD was given to supress the mycobacterium activity before chemotherapy. However the patient had febrile neutropenia after chemotherapy and died of septic shock. Both TBLN and NHL may occur with simillar sign and symptom and HPE. Further examinations have to be done to confirm the diagnosis of both disesases. Although ATD had given to prevent Tb infection progresivity. On 7 days after chemotherapy she had febrile neutropenia and lead to death due to septic shock.